CO2, quality of life and economic growth in mena countries - Tuncer Gövdeli (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
This paper examines thenexus between CO2 emissions, quality of life and economic growth in12 MENA countries over the period of 1970–2014. Empirical results show thatthere is unidirectional causality from CO2 emissions to economicgrowth. However, there is unidirectional causality from economic growth toquality of life. There is also bidirectional causality between CO2emissions and quality of life. This study shows that environmental policiesneed to recognize differences in MENA countries in order to increasesustainable economic growth and quality of life.